Sex chromatin and nuclear sex-specific appendages in the newborn - Sakhaullah, Sakhiyya (The Turkish Journal of Pediatrics, 1969)
A total of 81 newborns (41 male and 40 female) were studied for sex-chromatin frequencies in the buccal mucosa during the first three days of life and after three days. Fifteen female and 16 male newborns delivered vaginally (Group 1) were also studied for sex-specific appendages of the polymorphonuclear leukocytes. The remaining 25 female and 25 male newborns delivered by cesarean section (Group 2) were studied for sex-chromatin only. The incidence of mean sex-chromatin was low in the newborn females during the first three days of life compared to that after three days in both groups, and almost similar to the adult normal female control group. The incidence was identical in both the infant groups in both periods of life. It appears that the cause of suppression of sex-chromatin at birth is due to local changes in the buccal epithelium, and is related to normal physiology of the buccal mucosa.